Novel technology in sports biomechanics: some words of caution - Hughes, G. T. G.; Camomilla, V.; Vanwanseele, B.; Harrison, A. J.; Fong, D. T. P.; Bradshaw, E. J. (Sports Biomechanics, 2021)
Novel technology is often commercialised for direct sport applications. Researchers and practitioners need to understand the specific technology limits, best protocols for its intended use, as well as the accuracy, reliability, and specificity of the chosen measures before implementing the technologies in practice. In this editorial, two prevalent technologies with biomechanical applications have been discussed due to their relevance to sport biomechanics: the inertial measurement unit(s) and the smartphone sensors/app software. Emerging technological developments that are applicable to movement analysis offer exciting opportunities for biomechanics to bridge the gap between research and practice and allow Biomechanists to increasingly move away from the laboratory and to the field where athletes train and compete. The technologies could therefore provide opportunities to increase the ecological validity of the measurement obtained in sports biomechanics practice (research, applied). This changing operational environment could also assist biomechanics to have greater presence and perceived relevance to sport provided that the measures and interpretations can be trusted. The International Society of Biomechanics in Sport (ISBS) and this Journal are well positioned to guide and advise this evolution, to give the discipline and its members the best chance of success. This can be achieved through establishing standards for best practice, guided by a comprehensive review of what has already been learnt from the foundational research using these emerging technologies. Sports Biomechanics, therefore, encourages the International Society of Biomechanics in Sport (ISBS) to carry out research and provide a more comprehensive position statement on the use these technologies.